2021
DOI: 10.1186/s13227-021-00176-z
|View full text |Cite
|
Sign up to set email alerts
|

Early embryogenesis and organogenesis in the annelid Owenia fusiformis

Abstract: Background Annelids are a diverse group of segmented worms within Spiralia, whose embryos exhibit spiral cleavage and a variety of larval forms. While most modern embryological studies focus on species with unequal spiral cleavage nested in Pleistoannelida (Sedentaria + Errantia), a few recent studies looked into Owenia fusiformis, a member of the sister group to all remaining annelids and thus a key lineage to understand annelid and spiralian evolution and development. However, the timing of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 85 publications
6
79
0
Order By: Relevance
“…Antibodies against acetylated tubulin, the neuropeptide RFamide, and the monoamine transmitter serotonin label individual neurons and their processes, as well as tubulin-containing ciliary structures ( Schmidt-Rhaesa, Harzsch & Purschke, 2015 ). The specificity of the antibodies used in our study has previously been shown in various representatives of lophotrochozoan taxa including mollusks and annelids ( Voronezhskaya & Elekes, 1996 ; Dickinson, Croll & Voronezhskaya, 2000 ; Voronezhskaya, Tsitrin & Nezlin, 2003 ; Wanninger et al, 2005 ; Kristof, Wollesen & Wanninger, 2008 ; Dyachuk & Odintsova, 2009 ; Fischer, Henrich & Arendt, 2010 ; Carrillo-Baltodano et al, 2019 ; Kumar et al, 2020 ; Carrillo-Baltodano et al, 2021 ).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Antibodies against acetylated tubulin, the neuropeptide RFamide, and the monoamine transmitter serotonin label individual neurons and their processes, as well as tubulin-containing ciliary structures ( Schmidt-Rhaesa, Harzsch & Purschke, 2015 ). The specificity of the antibodies used in our study has previously been shown in various representatives of lophotrochozoan taxa including mollusks and annelids ( Voronezhskaya & Elekes, 1996 ; Dickinson, Croll & Voronezhskaya, 2000 ; Voronezhskaya, Tsitrin & Nezlin, 2003 ; Wanninger et al, 2005 ; Kristof, Wollesen & Wanninger, 2008 ; Dyachuk & Odintsova, 2009 ; Fischer, Henrich & Arendt, 2010 ; Carrillo-Baltodano et al, 2019 ; Kumar et al, 2020 ; Carrillo-Baltodano et al, 2021 ).…”
Section: Methodsmentioning
confidence: 77%
“… The diagram is based on the recent data on Sedentaria ( Kumar et al, 2020 ); Errantia ( Starunov, Voronezhskaya & Nezlin, 2017 ); Dinophiliformia ( this study ); Sipuncula ( Carrillo-Baltodano et al, 2019 ), and Oweniidae ( Carrillo-Baltodano et al, 2021 ). The phylogeny data is retrieved from ( Martín-Durán et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…: sections 69–78: morphdbase.de/?P_Beckers_20170310-M-96.1). According to some data [ 12 , 16 ], in the post-metamorphic stage of O. fusiformis, the dorsal root of the circumesophageal connectives contains 5HT-lir and FMRFamide-lir neurites, whereas the ventral root has only 5HT-lir neurites. In the adult oweniids, both the 5HT-lir and FMRFamide-lir nerves are also found in the rings of the anterior nerve center of G. oculata [ 13 ] and O. fusiformis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 7 ]. Members of the family Oweniidae have many unusual morphological, ultrastructural, and developmental characteristics [ 8 – 16 ]. Oweniids together with magelonids have been recently placed among the Palaeoannelida, a sister group to all remaining annelids [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies against acetylated tubulin, the neuropeptide RFamide, and the monoamine transmitter serotonin label individual neurons and their processes, as well as tubulin-containing ciliary structures (Schmidt-Rhaesa, Harzsch & Purschke, 2015). The specificity of the antibodies used in our study has previously been shown in various representatives of lophotrochozoan taxa including mollusks and annelids (Voronezhskaya & Elekes, 1996;Dickinson, Croll & Voronezhskaya, 2000;Voronezhskaya, Tsitrin & Nezlin, 2003;Wanninger et al, 2005;Kristof, Wollesen & Wanninger, 2008;Dyachuk & Odintsova, 2009;Fischer, Henrich & Arendt, 2010;Carrillo-Baltodano et al, 2019;Kumar et al, 2020;Carrillo-Baltodano et al, 2021).…”
Section: Immunocytochemistrymentioning
confidence: 55%